KESEPIAN DAN KEBIJAKSANAAN PADA REMAJA PEREMPUAN YANG MENGALAMI KEKERASAN SIBER - Riana Sahrani; Fransisca Iriani Roesmala Dewi; Wiwin Charolina Putri Basel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Cyber violence is one of the emerging threats in the digital era. It occurs more frequently among adolescent girls compared to boys. The impacts of cyber violence not only involve psychological disorders such as stress and depression but also increase the sense of loneliness among victims. On the other hand, wisdom is often regarded as a protective factor that can reduce loneliness. This study aims to examine the relationship between loneliness and wisdom among adolescent girls who are victims of cyber violence. A quantitative approach was employed, involving 200 adolescent girls aged 17–24 years. The participants were active social media users who had experienced cyber violence. The research instruments included the UCLA Loneliness Scale, the Brief Self-Assessed Kebijaksanaan Scale, and the Experiencing Cyber-Violence Scale. Data analysis was conducted using Pearson correlation and linear regression tests. The results revealed no significant relationship between wisdom and loneliness. Furthermore, wisdom showed no significant differences based on age, levels of loneliness, or duration of social media usage. These findings emphasize that loneliness among cyber violence victims is more influenced by other factors, such as social support and coping strategies, rather than internal characteristics like wisdom. This study also recommends cyber wisdom education as a preventive measure.